Facing COVID-19 in Ophthalmology Department. (2nd June 2020) - Romano, Mario R.; Montericcio, Alessio; Montalbano, Clara; Raimondi, Raffaele; Allegrini, Davide; Ricciardelli, Gabriella; Angi, Martina; Pagano, Luca; Romano, Vito
ABSTRACT: Purpose : To provide useful guidelines, targeted at ophthalmology professionals, to minimize COVID-19 infection of both health-care workers and patients. Methods : In this review we present updated literature merged with our experience from hospitals in Bergamo, the epicenter of the COVID-19 European outbreak. Results : Non-pharmaceutical interventions, hygienic recommendations and personal protective equipment to contain viral spread as well as a suggested risk assessment for postponement of non-urgent cases should be applied in ophthalmologist activity. A triage for ophthalmic outpatient clinic is mandatory. Conclusion : Ophthalmology practice should be reorganized in order to face COVID-19.